THE PERFORMING ART OF THE UZBEK TRADITIONAL INSTRUMENTS DURING THE YEARS OF INDEPENDENCE - Anvar Lutfullaev (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the art on Uzbek traditional instruments during the years of independence.